Efficacy of Yoga Exercises in pain relief in Primary Dysmenorrhea and Premenstrual Syndrome: a Literature Review - Suryaningtyas, Eka; Hartono, Soetanto; Wahyuni, Endang Sri; Muhammad, Heryanto Nur; Prasetya, Fika Indah; Nurvitasari, Rifzi Devi (IKIP Widya Darma Surabaya, 2024)
Objective: Women undergo various physiological and psychological changes during the reproductive stage, particularly during the menstrual cycle. Premenstrual symptoms, or dysmenorrhea, are the terms used to describe this. Menstrual pain is another term for dysmenorrhea, and primary dysmenorrhea often starts six months following menarche. Premenstrual symptoms are a complicated collection of symptoms that hurt a student's quality of life in the long run and their ability to succeed in school, participate in social activities, and maintain family relationships. Problems with both physical and mental health can benefit from yoga. Method: This study aims to assess the effectiveness of yoga activities in relieving pain in primary dysmenorrhea and premenstrual syndrome. In this investigation, a review of the literature was used. Six journal databases were searched for articles. Seven articles satisfied the requirements for inclusion. Result: The review's findings indicate that yoga practice is a viable substitute and is suggested as a simple, accessible, and non-invasive strategy for analgesia in primary dysmenorrhea and premenstrual syndrome. Novelty: This study shows the effectiveness of yoga exercises in reducing pain in primary dysmenorrhea and premenstrual syndrome for adolescents, especially women.